2015
DOI: 10.1016/j.celrep.2015.09.035
|View full text |Cite
|
Sign up to set email alerts
|

T-type Calcium Channel Regulation of Neural Tube Closure and EphrinA/EPHA Expression

Abstract: A major class of human birth defects arise from aberrations during neural tube closure (NTC). We report on a NTC signaling pathway requiring T-type calcium channels (TTCC) that is conserved between primitive chordates (Ciona) and Xenopus. With loss of TTCCs there is a failure to seal the anterior neural folds. Accompanying loss of TTCCs is an upregulation of EphrinA effectors. Ephrin signaling is known to be important in NTC, and ephrins can affect both cell adhesion and repulsion. In Ciona, ephrinA-d expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 60 publications
(86 reference statements)
3
33
0
Order By: Relevance
“…Large deletions of up to 23 kb of intervening DNA resulting from NHEJ between two CRISPR/Cas9-induced DSBs have been reported in Ciona (Abdul-Wajid et al 2015). For functional analyses of protein-coding genes, such deletions would more likely produce null mutations than small deletions resulting from the action of lone sgRNAs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Large deletions of up to 23 kb of intervening DNA resulting from NHEJ between two CRISPR/Cas9-induced DSBs have been reported in Ciona (Abdul-Wajid et al 2015). For functional analyses of protein-coding genes, such deletions would more likely produce null mutations than small deletions resulting from the action of lone sgRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…By using developmentally regulated cis -regulatory elements to drive Cas9 expression in specific cell lineages or tissue types, we were thus able to control the disruption of Ebf function with spatiotemporal precision. Following this proof-of-principle, tissue-specific CRISPR/Cas9 has rapidly propagated as a simple yet powerful tool to elucidate gene function in the Ciona embryo (Abdul-Wajid et al 2015; Cota and Davidson 2015; Segade et al 2016; Tolkin and Christiaen 2016). …”
Section: Introductionmentioning
confidence: 99%
“…The OTX dominant negative construct (OTX∷EnR) (Haeussler et al, 2010) was amplified and cloned into pCR8/GW/TOPO and recombined into ETR>RfA (Abdul-Wajid et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…This increases the odds of generating at least one out-of-frame indel, and the large deletions spanning multiple targets have been consistently observed in Ciona embryos ( Gandhi et al 2016), the largest deletion reported being ~13 kb ( Abdul-Wajid et al 2015). …”
Section: Sgrna Designmentioning
confidence: 99%
“…However, a chimeric “single-guide RNA” (sgRNA) is sufficient to mimic the roles of these two components ( Jinek et al 2012). This small but profound improvement has helped launch CRISPR/Cas9 as a cheap, simple, and efficient system for targeted mutagenesis in a remarkably wide variety of organisms ( Perry and Henry 2015; Iaffaldano et al 2016; Long et al 2016; Nomura et al 2016; Nymark et al 2016; Tian et al 2016), as well as in tunicates ( Sasaki et al 2014; Stolfi et al 2014; Abdul-Wajid et al 2015; Cota and Davidson 2015; Gandhi et al 2016; Segade et al 2016; Tolkin and Christiaen 2016). …”
mentioning
confidence: 99%